Olfactory search at high Reynolds number - Balkovsky, Eugene (The National Academy of Sciences, 2002)
Locating the source of odor in a turbulent environment—a common behavior for living organisms—is nontrivial because of the random nature of mixing. Here we analyze the statistical physics aspects of the problem and propose an efficient strategy for olfactory search that can work in turbulent plumes. The algorithm combines the maximum likelihood inference of the source position with an active search. Our approach provides the theoretical basis for the design of olfactory robots and the quantitative tools for the analysis of the observed olfactory search behavior of living creatures (e.g., odor-modulated optomotor anemotaxis of moths).